Rediscovering the Cooperative Enterprise: A Systematic Review of Current Topics and Avenues for Future Research - Camargo Benavides, Andres Felipe; Ehrenhard, Michel (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2021)
For decades, the cooperative enterprise (CE) produces market goods and/or provides services in the interest to its members, such as communities, customers, and suppliers. The upsurge of interest in social enterprises, and their balancing of social and economic interests, has also led to a renewed interest in CEs, often seen as a speciﬁc type of social enterprise. However, from an organizational perspective, this renewed interest has been both limited and scattered over a variety of ﬁelds. In this paper, we systematically review papers on CE in the mainstream organizational literature, deﬁned as literature in the ﬁelds of economics, business, management and sociology. Our review integrates and synthesizes the current topics in the mainstream organizational literature and provides a number of avenues for future research. In addition, we compare our ﬁndings in the organizational literature to the social issues literature as these appeared to be quite complimentary. We found multilevel studies, determination of social impact—in particular measurable impact, managerial practices for sustainable (organisational) development, and the entrepreneurial opportunity generation process as the four key avenues for future research.
Number: 5
Keywords: Coopératives; Entreprise; Entreprise sociale; Recherche; Réservé UdeM